Current Status of Novel Multifunctional Targeted Pt(IV) Compounds and Their Reductive Release Properties - Lingwen Xu; Xiangyu Kong; Xinzhi Li; Bin Zhang; Yuxiao Deng; Jinhu Wang; Chonggang Duan; Daizhou Zhang; Wentao Liu (Molecules, 2024)
Platinum-based drugs are widely used in chemotherapy for various types of cancer and are considered crucial. Tetravalent platinum (Pt(IV)) compounds have gained significant attention and have been extensively researched among these drugs. Traditionally, Pt(IV) compounds are reduced to divalent platinum (Pt(II)) after entering cells, causing DNA lesions and exhibiting their anti-tumor effect. However, the available evidence indicates that some Pt(IV) derivatives may differ from the traditional mechanism and exert their anti-tumor effect through their overall structure. This review primarily focuses on the existing literature regarding targeted Pt(II) and Pt(IV) compounds, with a specific emphasis on their in vivo mode of action and the properties of reduction release in multifunctional Pt(IV) compounds. This review provides a comprehensive summary of the design and synthesis strategies employed for Pt(II) derivatives that selectively target various enzymes (glucose receptor, folate, telomerase, etc.) or substances (mitochondria, oleic acid, etc.). Furthermore, it thoroughly examines and summarizes the rational design, anti-tumor mechanism of action, and reductive release capacity of novel multifunctional Pt(IV) compounds, such as those targeting p53-MDM2, COX-2, lipid metabolism, dual drugs, and drug delivery systems. Finally, this review aims to provide theoretical support for the rational design and development of new targeted Pt(IV) compounds.